Thermal conductivity of polypropylene/aluminum oxide nanocomposites prepared based on reactor granule technology. (8th September 2018) - Maira, Bulbul; Takeuchi, Kengo; Chammingkwan, Patchanee; Terano, Minoru; Taniike, Toshiaki
Abstract: A reactor granule technology (RGT) is a new method for the in-situ fabrication of polyolefin-based nanocomposites. It involves the impregnation and confinement of inorganic molecular precursors in the porosity of polyolefin reactor granule, and subsequent conversion of the precursors into highly dispersed inorganic nanoparticles during melt processing. In this contribution, the RGT was applied to develop thermally conductive polypropylene (PP)/aluminum oxide (Al2 O3 ) nanocomposites with the aid of two strategies. By melt-blending highly filled reactor granule with unfilled reactor granule, filler-rich and polymer-rich domains were created at around 10 μm scale, in which the filler-rich domains offered a thermally conductive pathway. The other strategy was based on tailoring the interfacial interaction between PP and Al2 O3 : An aluminum alkoxide precursor and a silane coupling agent were co-impregnated and converted into organically modified Al2 O3 nanoparticles. Both of the strategies successfully improved the thermal conductivity of the nanocomposites at a fixed Al2 O3 loading. The highest enhancement was achieved based on the interfacial modification using (2-phenylethyl)trimethoxysilane, where the thermal conductivity reached 0.74 W/m K at 20 wt% compared to 0.21 W/m K for pristine PP.